Квазиоптимальный прием сигналов некогерентного рассеяния - Емельянов, Леонид Яковлевич; Богомаз, Александр Викторович; Касымов, Идрис Магсимович (НТУ "ХПИ", 2015)
В результате проведенного для широкого диапазона высот и различного состояния космической погоды анализа спектральных характеристик некогерентно рассеянного (НР) ионосферой сигнала обоснована необходимость квазиоптимальной фильтрации полезного сигнала. Разработано устройство для квазиоптимальной фильтрации НР сигналов, предназначенное для работы в составе радара НР для повышения отношения сигнал/шум с минимальными искажениями спектра полезного сигнала.

The necessity of quasi-optimal filtering of the incoherent scatter (IS) signal was grounded as a result of analyzing the spectral characteristics of the signal. The analysis was carried out for a wide range of heights of the ionosphere and for different space weather. For the analysis, we used the parameters of the ionosphere calculated using the international ionosphere model IRI-2007 and experimental data obtained by IS radar of Institute of Ionosphere (Kharkiv). Principles of filtering were developed. We have proposed to use low-pass filters with different characteristics to filter IS signals from several altitude ranges. A choice of a number of altitude ranges (number of filters) and their boundaries for each filter depends on the specific conditions of the ionosphere parameters measurements. If there are several processing units, the same number of filters can be simultaneously used for filtering the receiver output signal. With a single processing device, outputs of the filters are switched in moments of radar scan corresponding to the boundaries of altitude ranges. A device for the quasi-optimal filtering IS signals was developed for operation in the IS radar to improve the signal-to-noise ratio with minimal distortion of the useful signal spectrum.
Keywords: ионосфера; радар некогерентного рассеяния; квазиоптимальная фильтрация; полезный НР сигнал; гелиофизические условия; ionosphere; incoherent scatter radar; quasi-optimal filtering device